Wettability and adhesion of nanotubes applied to the surface of titanium implants by anodic oxidation - Rogério de Lima ROMEIRO; Jorge Luiz ROSA; Lyncoln da Silva SIQUEIRA; Marcos GIOVANETTI; Davi Romeiro AQUINO; Patricia Fretes WOOD; Sandra Giacomin SCHNEIDER; Gustavo Grolli KLEIN (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to evaluate the wettability and adhesion of self-organized TiO2 nanotubes formed on the surface of 8 commercially pure titanium (CP-Ti) disks and 12 dental implants (n = 12) by anodization in a glycerol-H2O (50-50 v/v) electrolyte containing NH4F. Two disk specimens were not submitted to anodization (controls). The nanotubes thus obtained had average dimensions of 50 nm in diameter by 900 nm in length. The treated disk specimens were stored for 2, 14 and 35 days (n = 2), and the wettability of their surfaces was evaluated with a goniometer at the end of each storing period. The adhesion of nanotubes to titanium was evaluated by field emission scanning electron microscopy after subjecting the 12 implants to a simulation of clinical stress in two-part synthetic bone blocks. After installing the implants with the application of an insertion torque, the two halves of the block were separated, and the implants were removed. The nanotubes remained adhered to the substrate, with no apparent deformation. The contact angles after 14 days and 35 days were 16.47° and 17.97°, respectively, values significantly higher than that observed at 2 days, which was 9.24° (p < 0.05). It was concluded that the method of anodic oxidation tested promoted the formation of a surface suitable for clinical use, containing nanotubes with levels of wettability and adhesion to titanium compatible with those obtained by other methods found in the literature. The wettability, however, did not prove stable over the tested storage periods.